Elytra coupling of the ladybird Coccinella septempunctata functions as an energy absorber in intentional falls. (31st August 2021) - Zhang, Jie; Yuan, Qiufeng; Jiang, Yiling; Pang, Hong; Rajabi, Hamed; Wu, Zhigang; Wu, Jianing
Abstract: Some insects, such as bees, wasps, and bugs, have specialized coupling structures to synchronize the wing motions in flight. Some others, such as ladybirds, are equipped with coupling structures that work only at rest. By locking elytra into each other, such structures provide hindwings with a protective cover to prevent contamination. Here, we show that the coupling may play another significant role: contributing to energy absorption in falls, thereby protecting the abdomen against mechanical damage. In this combined experimental, numerical and theoretical study, we investigated free falls of ladybirds ( Coccinella septempunctata ), and discovered that upon collision to the ground, the coupling may fail and the elytra may unlock. This unlocking of the coupling increased the energy absorption by 33%, in comparison to when the elytra remain coupled. Using micro-computed tomography scanning, we developed comparative models that enabled us to simulate impact scenarios numerically. Our results showed that unlocking of the coupling, here called elytra splitting, reduces both the peak impact force and rebound velocity. We fabricated the insect-inspired coupling mechanism using 3D printing and demonstrated its application as a damage preventing on system for quadcopters in accidental collisions.